Body Figure Perception And Relation With Eating Habits In Turkish Adults - Aysun Mara Uysal; Can Öner; Huseyin Cetin; Engin Ersin Simsek (Universitas Muhammadiyah Malang, 2021)
Body image problems are associated with several mental health problems: low self-esteem, depression, and eating disorders. This study aimed to determine the rate of impaired body figure perception and its relation with eating habits in Turkish adults. This cross-sectional study was carried with 446 participants. To determine body figure perception Stunkart Figure Scale was used. Dutch Eating Attitude Questionnaire was applied to determine the eating habits of all participants. Study data were analyzed with SPSS 21.0 package program. The concordance between Body Mass Index (BMI) and Stunkart Figure Scale was 66% (r=0,660; p=0,000). The concordance between BMI and Stunkart Figure scale gradually decreases from weak to morbidly obese. The mean scores obtained by the participants from the DEAQ showed that only external eating and restrictive eating behaviors of the participants are affected by the compliance with the scale (p =0,000; p=0,000 respectively). Concordance of body figure perception with actual BMI was good level in more than half of the participants and only extrinsic and restrictive eating behavior is affected by this concordance. Individuals need to make healthy evaluations about their bodies in terms of individual and public health to control weight gain.